WebRTC integrator's guide : successfully build your very own scalable WebRTC infrastructure quickly and efficiently - Altanai (Community experience distilled., 2014)
This book is for programmers who want to learn about real-time communication and utilize the full potential of WebRTC. It is assumed that you have working knowledge of setting up a basic telecom infrastructure as well as basic programming and scripting knowledge.